Accuracy of complete compression ultrasound in ruling out suspected deep venous thrombosis in the ambulatory setting - Sevestre, Marie-Antoinette; Labarère, José; Casez, Pierre; Bressollette, Luc; Taiar, Mébarka; Pernod, Gilles; Quéré, Isabelle; Bosson, Jean-Luc (Thrombosis and Haemostasis, 2009)
Evidence on the safety of complete compression ultrasound for ruling out deep venous thrombosis (DVT) is derived from studies conducted in tertiary care centers, although most patients with suspected DVT are managed in the ambulatory office setting. It was the objective of this study to estimate the rate of venous thromboembolism when anticoagulant therapy is withheld from ambulatory patients with normal findings on a single complete compression ultrasound. As part of a prospective cohort study, 3,871 ambulatory patients with clinically suspected DVT were enrolled by 255 board-certified vascular medicine physicians practicing in private offices in France. Compression ultrasound of the entire lower extremities was performed using a standardised examination protocol. Anticoagulant therapy was withheld from patients with negative findings on compression ultrasound, and 1,254 of them were randomly selected for follow-up. The main outcome measure was the three-month incidence of symptomatic venous thromboembolic events confirmed by objective testing. DVT was detected in 1,023 patients (26.4%),including 454 (11.7%) and 569 (14.7%) cases of proximal and isolated distal DVT, respectively. Of the 1,254 patients with negative results sampled for follow-up, six received anticoagulant therapy during follow-up and five were lost to follow-up. Five of 1,243 patients (0.4%, 95% confidence interval [CI], 0.1–0.9) experienced non-fatal symptomatic venous thromboembolic events (pulmonary embolism in two patients and DVT in three patients) and eight of 1,254 patients (0.6%, 95% CI, 0.3–1.2) died during the three-month follow-up. In conclusion, anticoagulant therapy can be safely withheld after negative complete compression ultrasound without further testing in the ambulatory office setting.
Keywords: Venous thrombosis; veins/ ultrasonography; cohort studies